Prolonged varicella-zoster virus reinfection in an adult after unrelated cord blood transplantation - Masahiro Oka; Makoto Kunisada; Yuichiro Oba; Atsuo Okamura; Chikako Nishigori (Wolters Kluwer Medknow Publications, 2012)
Most varicella-zoster virus (VZV) infections after cord blood transplantation (CBT) present as localized herpes zoster. Here, we report a case of VZV reinfection in an adult patient after CBT that appeared clinically to be varicella. A 50-year-old Japanese man underwent CBT for the management of acute lymphoblastic leukemia. Seventeen months later, he developed a small number of vesicles with umbilicated centers. A skin biopsy showed an intraepidermal blister containing degenerated balloon cells. Subsequently, the skin eruption developed over his entire body. The patient was treated with intravenous acyclovir for 5 days, followed by oral valacyclovir for 9 days. It took more than 3 weeks for most of the skin lesions to scab. Serum levels of anti-VZV IgG on days 3 and 33 after the onset of the skin eruption were negative and 260 mIU/ml, respectively. Serum anti-VZV IgM on days 3 and 33 was not detected. Our patient was diagnosed with VZV reinfection.